Effect of Seed Priming with PGPR on Germination, Mean Emergence Time and Vigour of Paddy under Osmotic Stress - Hussain, Saddam; Rao, K. Prasada; Marker, Shailesh; Khan, Farooq A. (International Journal of Economic Plants, 2025)
The experiment was carried out during kharif (2022) at SHUATS, Naini, Prayagraj with 16 treatments comprised of PGPRs (PAR-6, PES-2, PR-7, PR-12 and PR-15) and PEG to assess the effect of seed priming with PGPRs on certain seed germination attributes of paddy under osmotic stress. All the treatments were replicated thrice and statistical design CRD was followed. Seeds of paddy variety MTU-1172 were treated with different concentrations of PGPRs followed by drying in the dark for 2–3 hours at room temperature. Seeds were sown in petri-dishes lined with blotting paper and different seed germination parameters were recorded. Findings of the experiment revealed that the seed priming with PES-2 showed maximum germination percentage (80%), germination index (7.33), seedling dry biomass (0.11) and vigour index-II (8.8), while as, seed priming with PAR-6 showed maximum value of MET (5.17 days). These findings may be attributed to the fact that pre-sowing of seeds triggered resistance under osmotic stress. Seedling vigour index-I were found maximum of 13.20, 14.77, 16.55 with treatment PR-7 plus PEG (-2bar), respectively at 7th, 14th and 21st days of measurement. Results also indicated that the PGPRs have similar effect like KNO3, SiO2 and SA, which might have to increase the seedling characters and vigour index-II in paddy rice. It may be concluded that the isolate PR-7 emerged as a superior PGPR to reduce the PEG-induced osmotic stress of -2 bars. Thus, farmers can use recommended eco-friendly, cost-effective and easily available PGPR for enhancing the productivity of paddy.